Effect of Shallow Tubewell Irrigation on Ground Water Table of Hilsa Block of Nalanda District (Bihar) - Sinha, B.P.; Kumar, Sunil (Journal of Soil and Water Conservation, 2022)
Ground water in Hilsa block of Nalanda, Bihar occurs in Uncon- fined aquifer at shallow depth of 20-60m and in deep confined aquifer beyond 100n; depth. Water present in unconfined aquifer at shallow depth is being extensively developed and utilised for intensive cultivation by constructing shallow tube wells which has resulted in lowering down of the ground water table of the area.